Prevalence and trends in mono- and co-infection of COVID-19, influenza A/B, and respiratory syncytial virus, January 2018–June 2023 - Lee, Min Kyung; Alfego, David; Dale, Suzanne E. (Frontiers in Public Health, 2023)
Objectives This study aimed to determine the impact of the COVID-19 pandemic on the overall prevalence and co-infection rates for COVID-19, influenza A/B, and respiratory syncytial virus in a large national population. Methods We conducted a retrospective review of 1,318,118 multi-component nucleic acid amplification tests for COVID-19, influenza A/B, and RSV performed at Labcorp® sites from January 2018 to June 2023, comparing positivity rates and co-infection rates by age, sex, and seasonality. Results In 2021–2023, 1,232 (0.10%) tested positive for COVID-19 and influenza A/B, 366 (0.03%) tested positive for COVID-19 and RSV, 874 (0.07%) tested for influenza A/B and RSV, and 13 (0.001%) tested positive for COVID-19, influenza A/B, and RSV. RSV positivity rates were particularly higher in Q2 and Q3 of 2021 and in Q3 of 2022. Higher influenza A positivity proportions were found in Q4 of 2021 and again in Q2 and Q4 of 2022. Influenza B positivity had been minimal since the start of the pandemic, with a slight increase observed in Q2 of 2023. Conclusion Our findings highlight the need for adaptability in preparation for upper respiratory infection occurrences throughout the year as we adjust to the COVID-19 pandemic due to the observed changes in the seasonality of influenza and RSV. Our results highlight low co-infection rates and suggest heightened concerns for co-infections during peaks of COVID-19, influenza, and RSV, which may perhaps be reduced.